Stratifikasi Sosial Masyarakat Petani Desa Berdasarkan Kepemilikan Tanah - Ken Izzah Zuraidah (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2022)
Village community life is generally known to be more open to one another. The majority of the village community's source of life comes from daily work activities, namely farming in the fields. Many people think that the village community who is the farmer is the owner of the land. However, the reality is that most of the villagers are only agricultural laborers who work on land or rice fields belonging to people who do not even live in the village. So that the income earned is also not much, and becomes a consequence in society. Like the division of layers or classes in the society of a village, most of the lower class people are rarely prioritized or do not respond to their existence in the area. Meanwhile, the upper and middle class people actually have a very strong relationship in a society.